Felix König and the European science community across enemy lines during the First World War - Rack, Ursula (The Polar Journal, 2014)
This paper explores the process of international cooperation within a scientific community in wartime, focusing on Felix König. He was an Austrian participant in the “Second German Antarctic Expedition” (1911-1912) led by Wilhelm Filchner. Later, he organised his own Antarctic expedition which had much support from leading polar explorers of his time including Fridtjof Nansen, Otto Nordenskjöld and Roald Amundsen. Because of the war, however, König was not allowed to begin his expedition. Instead, he joined the Austro-Hungarian Army, serving in Galicia (Poland). As a result, König became a prisoner of war in Siberia, prompting his mother to contact many of the polar explorers to help her free him. Her attempts, which failed, were not random futile pleadings from a worried mother since she was aware that the science community assisted in attempting to free prisoners. Transnational support of scientists across enemy boundaries was a further example of a civilised attempt to maintain contact despite the war. Members of the international scientific community sent books and other material into camps so that the officers could organise lectures and improve their studies. This became a welcome sign of civilisation for the prisoners who were often surrounded by circumstances of barbarism, food shortages and inadequate medical care. The sources for this study are the original letters, which are now in a private collection, written by the science community and Felix König himself.